2021
DOI: 10.1088/1748-9326/ac3bff
|View full text |Cite
|
Sign up to set email alerts
|

Impact of North America snow cover on tropical cyclogenesis over the western North Pacific

Abstract: This study reveals a connection of summer–fall (JJASO) tropical cyclone (TC) genesis over the western North Pacific (WNP) to preceding boreal spring (MAM) North America snow cover (NASC). Sea surface temperature (SST) anomalies in the tropical central Pacific and subtropical eastern Pacific play a crucial role in relaying influence of the MAM NASC on the following JJASO WNP TC genesis frequency. The increased NASC leads to a decrease in upward sensible heat flux and the atmospheric cooling over the North Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Major variations in monsoons and tropical cyclones (TCs) can cause serious natural disasters, and the characteristics and mechanisms of anomalous monsoons and TCs have become important topics in climate variability and prediction studies (Knutson et al 2010, Vishnu et al 2016, Cao et al 2021, Basconcillo and Moon 2022. Variations of the North American summer monsoon (NASM) and North Atlantic tropical cyclone (NATC) activities strongly influence climate anomalies in North America, with serious potential risk to life and property (Adams et al 1997, Higgins et al 1997, Rappaport 2000, Barlow et al 2011, Klotzbach et al 2018, Boos et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Major variations in monsoons and tropical cyclones (TCs) can cause serious natural disasters, and the characteristics and mechanisms of anomalous monsoons and TCs have become important topics in climate variability and prediction studies (Knutson et al 2010, Vishnu et al 2016, Cao et al 2021, Basconcillo and Moon 2022. Variations of the North American summer monsoon (NASM) and North Atlantic tropical cyclone (NATC) activities strongly influence climate anomalies in North America, with serious potential risk to life and property (Adams et al 1997, Higgins et al 1997, Rappaport 2000, Barlow et al 2011, Klotzbach et al 2018, Boos et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the forecast accuracy of TCs, several attempts have been made to understand the ocean's role in cyclogenesis (Trenberth et al ., 2007; Pianezze et al ., 2018; Singh and Roxy, 2022). Similarly, some studies conducted in Europe and the United States revealed the importance of land characteristics such as surface roughness, snow cover, and soil moisture (SM) in the evolution of cyclones (Belušić et al ., 2019; Zhang et al ., 2019; Cao et al ., 2021). The intensity and heavy rainfall associated with the TCs have been attributed to multiscale and non‐linear interactions with weather systems, topography, inherent model error, and land surface conditions (Atallah and Bosart, 2003; May et al ., 2008; Kieu et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%